Continuous thermosalinograph oceanography along RV HEINCKE cruise track HE572 - Mario Hoppmann; Sandra Tippenhauer; Jennifer Dannheim (PANGAEA, 2022)
Raw data acquired by an SBE21 thermosalinograph and an auxiliary SBE38 temperature sensor (Sea-Bird Scientific, USA) installed in an underway seawater flow-through system on board RV Heincke were processed to yield a calibrated and validated data set of seawater temperature and salinity along the cruise track. The seawater inlet is located at a depth of 2 m. The raw hexadecimal data were downloaded from the DAVIS SHIP data base (https://dship.awi.de) at a resolution of 1 s, and converted to temperature and conductivity using the pre-deployment factory calibration coefficients. The converted data were averaged to 1 min values, outliers were removed, and sensor drift was corrected using coefficients obtained from a post-season calibration performed at Sea-Bird at the end of the measurement season. Salinity was calculated from internal temperature, conductivity and pressure according to the PSS-78 Practical Salinity Scale. Processed data are provided as 1 min means of seawater temperature, conductivity and salinity, aligned with position data taken from the master track. Quality flags are appended according to the SeaDataNet Data Quality Control Procedures (version from May 2010). More details are described in the attached processing report.